Застосування методів регуляризації до ідентифікації параметрів розподілених процесів у задачах контролю промислових викидів у атмосферу - Selin, A. N.; Palti, I. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Comparative investigation of iterative regularization and quasisolution techniques for control over harmful industrial air venting is presented. A combined technique is proposed which being based on using both these techniques makes it possible to extend the quasisolution technique application area with its high precision and noise resistance remaining.